ORGANIZATION OF CONTROL SECURITY WIRELESS COMPUTER NETWORK BASED ON FUZZY NETWORKS - Юдін, Олександр Миколайович; Хлапонін, Юрій Іванович (Science-based technologies, 2016)
In the article the solution of the problem of security control node wireless computer network, which is based on the use of the apparatus of fuzzy sets. Powered by the article approach is the basis for its automation that will improve the efficiency of control units and speed of action network administrator. The approach allows to build a system of security control wireless computer network based on neuro-fuzzy (hybrid) network, which is different adaptability, ease of use, the ability to better identify the sequence analysis of vulnerabilities in a wireless computer network nodes. The feature of the proposed approach is taken into account the dynamic nature of the wireless computer network.